Tacrine-Trolox Hybrids: A Novel Class of Centrally Active, Nonhepatotoxic Multi-Target-Directed Ligands Exerting Anticholinesterase and Antioxidant Activities with Low In Vivo Toxicity - Nepovimova, Eugenie; Korabecny, Jan; Dolezal, Rafael; Babkova, Katerina; Ondrejicek, Ales; Jun, Daniel; Sepsova, Vendula; Horova, Anna; Hrabinova, Martina; Soukup, Ondrej; Bukum, Neslihan; Jost, Petr; et al. (Journal of medicinal chemistry, 2015)
Coupling of two distinct pharmacophores, tacrine and trolox, endowed with different biological properties, afforded 21 hybrid compounds as novel multifunctional candidates against Alzheimer's disease. Several of them showed improved inhibitory properties toward acetylcholinesterase (AChE) in relation to tacrine. These hybrids also scavenged free radicals. Molecular modeling studies in tandem with kinetic analysis exhibited that these hybrids target both catalytic active site as well as peripheral anionic site of AChE. In addition, incorporation of the moiety bearing antioxidant abilities displayed negligible toxicity on human hepatic cells. This striking effect was explained by formation of nontoxic metabolites after 1 h incubation in human liver microsomes system. Finally, tacrine-trolox hybrids exhibited low in vivo toxicity after im administration in rats and potential to penetrate across blood-brain barrier. All of these outstanding in vitro results in combination with promising in vivo outcomes highlighted derivative 7u as the lead structure worthy of further investigation.
Keywords: kinetika; Microsomes, Liver; katalýza; Hepatocytes; Models, Molecular; Acetylcholinesterase; Rats; injekce intramuskulární; ligandy; scavengery volných radikálů; cholinesterasové inhibitory; acetylcholinesterasa; Antioxidants; Blood-Brain Barrier; takrin; Tacrine; Cholinesterase Inhibitors; mužské pohlaví; Catalysis; Rats, Wistar; krysa rodu Rattus; Injections, Intramuscular; antioxidancia; hepatocyty; Ligands; molekulární modely; zvířata; Humans; racionální návrh léčiv; Free Radical Scavengers; Kinetics; chromany (dihydrobenzopyrany); Chromans; jaterní mikrozomy; potkani Wistar; Drug Design; hematoencefalická bariéra; lidé; Male; Animals